Mechanical Properties, Physical Properties and VOC Emissions of Three-Layer Particleboards with Recycled Automotive Plastics in the Core Layer - Darabošová, Anna; Bubeníková, Tatiana; Čabalová, Iveta; Badida, Miroslav; Olgun, Çağrı; Tor, Önder; Öncel, Mustafa (MDPI AG, 2025)
The growing volume of plastic waste from end-of-life vehicles presents environmental concerns, driving efforts to integrate recycled plastics. This study investigates the possibility of using recycled plastic from automotive parts (painted and unpainted bumpers, fuel tanks) as a 10% filler in the core layer of three-layer particleboards (P) and evaluates its impact on physical properties (water absorption—WA and thickness swelling—TS), mechanical properties (internal bonding strength—IB, modulus of rupture—MOR, modulus of elasticity—MOE and screw driving torque—SDT) and volatile organic compounds—VOC emissions. The boards were produced using conventional hot-pressing technology and analyzed according to applicable standards. Based on the results, the density of the reference (P) was 0.72 g·cm−3, while wood–plastic composites ranged from 0.70 g·cm−3 to 0.72 g·cm−3. After 24 h, WA reached 40% for reference (P) and from 36.9% (for (P) containing unpainted bumpers) to 41.9% (for (P) containing fuel tanks). TS reached 18% for (P) and from 16.8% (for (P) containing unpainted bumpers and fuel tanks) to 18.1% (for (P) containing painted bumpers). Plastic is a hydrophobic material and it is assumed that by increasing the proportion of plastic filler in the particleboards, the WA and TS of prepared boards will decrease. From the point of view of mechanical properties, values for (P) containing plastic filler were slightly lower compared to reference (P). The lowest value of IB (0.39 MPa) were reached for (P) containing painted bumpers. Plastic surface treatment could interfere with adhesion between the plastic and adhesive, weakening the bond in the core layer. For this reason, is preferable to use unpainted fillers, which provide better adhesive properties and higher structural integrity. VOC emissions from wood components consisted primarily of monoterpenes such as α-pinene, 3-carene and limonene. Adding 10% plastic to the particleboard did not increase overall VOC emissions. On the other hand, combining wood and plastic particles resulted in a reduction in overall VOC emissions. The findings confirm that recycled automotive plastics can be effectively incorporated into particleboards, maintaining standard performance while reducing reliance on virgin wood materials, making them a viable and sustainable alternative for furniture and interior applications.
Keywords: Article